Quantifying the resilience of an urban traffic-electric power coupled system - Fotouhi, Hossein; Moryadee, Seksun; Miller-Hooks, Elise (Reliability engineering & system safety, 2017)
Transportation system resilience has been the subject of several recent studies. To assess the resilience of a transportation network, however, it is essential to model its interactions with and reliance on other lifelines. Prior works might consider these interactions implicitly, perhaps in the form of hazard impact scenarios wherein services from a second lifeline (e.g. power) are precluded due to a hazard event. In this paper, a bi-level, mixed-integer, stochastic program is presented for quantifying the resilience of a coupled traffic-power network under a host of potential natural or anthropogenic hazard-impact scenarios. A two-layer network representation is employed that includes details of both systems. Interdependencies between the urban traffic and electric power distribution systems are captured through linking variables and logical constraints. The modeling approach was applied on a case study developed on a portion of the signalized traffic-power distribution system in southern Minneapolis. The results of the case study show the importance of explicitly considering interdependencies between critical infrastructures in transportation resilience estimation. The results also provide insights on lifeline performance from an alternate power perspective. •Model interdependent infrastructure systems.•Provide method for quantifying resilience of coupled traffic and power networks.•Propose bi-level, mixed-integer, stochastic program.•Take a multi-hazard, stochastic futures approach.